Medication Bezoar Causing acute Gastric Outlet Obstruction: A Case Report - Mazid, Md Abdul (Journal of Bangladesh College of Physicians and Surgeons, 2016)
Medication bezoars are rare and are composed of medications and/or medication vehicles. Rarely, medication bezoars can cause serious problems due to complications such as perforation, obstruction, haemorrhage. A 60 years old woman presented with 10 days history of epigastric pain, weakness and postprandial non-bilious vomiting. Her abdominal ultrasonography showed strong post acoustic shadow noted within 1st part of duodenum possibly foreign body. Upper gastrointestinal endoscopy was performed and a bezoar of tablet of aluminum hydroxide was extracted. The patient had uneventful recovery. Acute gastric outlet obstruction is relatively uncommon and mostly due to foreign bodies related to food impaction, with meat being the most frequent culprit. The diagnostic approach to acute gastric outlet obstruction is similar to other cause of GOO. However, therapeutic options differ for each patient. The diagnosis should be made in prompt time to prevent life threatening complications due obstruction and/or effect of medication forming bezoar. J Bangladesh Coll Phys Surg 2015; 33(3): 177-180